The impact of international health worker migration and recruitment on health systems in source countries: stakeholder perspectives from Colombia, Indonesia, and Jordan - Sax dos Santos Gomes, Lila; Efendi, Ferry; Putri, Nuzulul Kusuma; Bolivar-Vargas, Mery; Saadeh, Rami; Villarreal, Pedro A.; Aye, Thit Thit; De Allegri, Manuela; Lohmann, Julia (The international journal of health planning and management, 2024)
Introduction To address domestic shortages, high-income countries are increasingly recruiting health workers from low- and middle-income countries. This practice is much debated. Proponents underline benefits of return migration and remittances. Critics point in particular to the risk of brain drain. Empirical evidence supporting either position is yet rare. This study contributes to filling this gap in knowledge by reporting high-level stakeholders' perspectives on health system impacts of international migration in general, and active recruitment of health workers in specific, in Colombia, Indonesia, and Jordan. Method We used a multiple case study methodology, based on qualitative methods integrated with information available in the published literature. Results All respondents decried a lack of robust and detailed data as a serious challenge in ascertaining their perspectives on impacts of health worker migration. Stakeholders described current emigration levels as not substantially aggravating existing health workforce availability challenges. This is due to the fact that all three countries are faced with health worker unemployment grounded in unwillingness to work in rural areas and/or overproduction of certain cadres. Respondents, however, pleaded against targeting very experienced and specialised individuals. While observing little harm of health worker migration at present, stakeholders also noted few benefits such as brain gain, describing how various barriers to skill enhancement, return, and reintegration into the health system hamper in practice what may be possible in theory. Conclusion Improved availability of data on health worker migration, including their potential return and reintegration into their country of origin's health system, is urgently necessary to understand and continuously monitor costs and benefits in dynamic national and international health labour markets. Our results imply that potential benefits of migration do not come into being automatically, but need in-country supportive policy and programming, such as favourable reintegration policies or programs targeting engagement of the diaspora.
Zuerst veröffentlicht: 07. Februar 2024
Gesehen am 25.06.2024
Keywords: Kolumbien; Indonesien; Es Safı -- Jordanien